Research on the Identification Standard of Public Body in the Sense of ASCM (Asian Journal of Social Science Studies, 2022)
Under the trend of economic globalization, the foreign import and export trade of all countries in the world is bound to be more prosperous in the end. More than 40 years ago, an old man overcame all the opinions and made a major historical strategic choice to implement reform and opening up. After that, China also continued to implement the "going global" strategy. However, in the foreign trade of China's state-owned enterprises, they were frequently subjected to countervailing investigations by some countries importing raw materials and products led by the United States. These countries often identify Chinese state-owned enterprises as public body in their countervailing decisions, which has greatly damaged the interests of Chinese state-owned enterprises. In the identification of subsidy measures, the identification of "public body" has become an important part, which leads to the problem of how to identify "public body". On this basis, this paper first introduces the relevant background to clarify the importance of the identification standards of "public body", then systematically explains and evaluates the relevant identification standards existing in WTO practice, and finally puts forward its own suggestions for the improvement of the existing identification standards of "public body" and Chinese Countermeasures on this basis.